The performance of stylosanthes species in different production systems in Nigeria - Agishi, E.C.; Leeuw, P.N. de (International Livestock Centre for Africa, 1986)
Summarises the performance of three species of stylosanthes, viz, S. guianensis cvs Cook and Schofield, S. hamata cv. Verano and S. humilis under different production systems in Nigeria, such as in pure legume pastures, mixed pastures, with crops, in rangeland and under seed production.